2022
DOI: 10.3389/fimmu.2022.958581
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of TMPRSS2-mediated priming of SARS-CoV-2 by lactoferricin

Abstract: In addition to vaccines, there is an urgent need for supplemental antiviral therapeutics to dampen the persistent COVID-19 pandemic caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The transmembrane protease serine 2 (TMPRSS2), that is responsible for proteolytic priming of the SARS-CoV-2 spike protein, appears as a rational therapeutic target. Accordingly, selective inhibitors of TMPRSS2 represent potential tools for prevention and treatment of COVID-19. Previously, we identified th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…MNT coupled to in-cell ELISA was found to be equally sensitive to PRNT in evaluating NAbs in tested sera [ 69 ], and neutralization titers determined by MNT significantly correlated with S protein-binding antibody titers determined by standard ELISA [ 68 , 70 ]. Since MNT uses an authentic virus that can undergo several replication cycles, the assay can be easily adapted to measure the inhibitory effect of various antiviral drugs or inhibitors of pathways that are employed by the virus for cell entry, replication or egress [ 67 , 69 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Virus-neutralization Assays: the Gold Standard?mentioning
confidence: 99%
“…MNT coupled to in-cell ELISA was found to be equally sensitive to PRNT in evaluating NAbs in tested sera [ 69 ], and neutralization titers determined by MNT significantly correlated with S protein-binding antibody titers determined by standard ELISA [ 68 , 70 ]. Since MNT uses an authentic virus that can undergo several replication cycles, the assay can be easily adapted to measure the inhibitory effect of various antiviral drugs or inhibitors of pathways that are employed by the virus for cell entry, replication or egress [ 67 , 69 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Virus-neutralization Assays: the Gold Standard?mentioning
confidence: 99%
“…For any route of the virus entry, the importance of the proteolytic destabilizing cleavage of S1/S2 junction (see Section 3 , gaining U from D states in RBDs) and subsequent proteases-induced transition of S2 subunit to fusogenic configuration should be emphasized [ 66 ]. In silico and cell culture studies showed peptidomimetic binding compounds as well as lactoferricin and lactoferrin hinder the infectivity of SARS-CoV-2 significantly through inhibition of TMPRSS2-induced priming of S protein [ 67 , 68 ]. However, a recent study on HEK293T cells revealed that both TMPRSS2 and metalloproteases, particularly ADAM17, individually or co-operatively, promote activation of S2′ segment of S protein and syncytia formation in infection by SARS-CoV-2 and its emerging variants of concern [ 69 ].…”
Section: Proteases Play a Pivotal Role In Various Models Of Sars-cov-...mentioning
confidence: 99%
“…For any route of the virus entry, the importance of the proteolytic destabilizing cleavage of S1/S2 junction (see above, gaining U from D states in RBDs) and subsequent proteases-induced transition of S2 subunit to fusogenic configuration should be emphasized [59]. In Silico and cell culture studies showed peptidomimetic binding compounds as well as lactoferricin and lactoferrin hinder the infectivity of SARS-CoV2 significantly through inhibition of TMPRSS2-induced priming of S protein [60,61]. However, a recent study on HEK293T cells revealed that both TMPRSS2 and metalloproteases, particularly ADAM17, individually or co-operatively, promote activation of S2' segment of S protein and syncytia formation in infection by SARS-CoV2 and its emerging variants of concern [62].…”
Section: Proteases Play a Pivotal Role In Various Models Of Sars-cov2...mentioning
confidence: 99%